Game performance evaluation in male goalball players - Molik, B.; Morgulec-Adamowicz, N.; Kosmol, A.; Perkowski, K.; Bednarczuk, G.; Skowronski, W.; Gomez, M. A.; Koc, K.; Rutkowska, I.; Szyman, R. J. (Journal of Human Kinetics, 2015)
Goalball is a Paralympic sport exclusively for athletes who are visually impaired and blind. The aims of this study were twofold: to describe game performance of elite male goalball players based upon the degree of visual impairment, and to determine if game performance was related to anthropometric characteristics of elite male goalball players. The study sample consisted of 44 male goalball athletes. A total of 38 games were recorded during the Summer Paralympic Games in London 2012. Observations were reported using the Game Efficiency Sheet for Goalball. Additional anthropometric measurements included body mass (kg), body height (cm), the arm span (cm) and length of the body in the defensive position (cm). The results differentiating both groups showed that the players with total blindness obtained higher means than the players with visual impairment for game indicators such as the sum of defense (p = 0.03) and the sum of good defense (p = 0.04). The players with visual impairment obtained higher results than those with total blindness for attack efficiency (p = 0.04), the sum of penalty defenses (p = 0.01), and fouls (p = 0.01). The study showed that athletes with blindness demonstrated higher game performance in defence. However, athletes with visual impairment presented higher efficiency in offensive actions. The analyses confirmed that body mass, body height, the arm span and length of the body in the defensive position did not differentiate players` performance at the elite level.